Long History, Deep Time. Deepening Histories of Place - McGrath, Ann (ANU Press, 2015)
The vast shape-shifting continent of Australia enables us to take a long view of history. We consider ways to cross the great divide between the deep past and the present. Australia's human past is not a short past, so we need to enlarge the scale and scope of history beyond 1788. In ways not so distant, these deeper times happened in the same places where we walk today. Yet, they were not the same places, having different surfaces, ecologies and peoples. Contributors to this volume show how the earth and its past peoples can wake us up to a sense of place as history - as a site of both change and continuity. This book ignites the possibilities of what the spaces and expanses of history might be. Its authors reflect upon the need for appropriate, feasible timescales for history, pointing out some of the obstacles encountered in earlier efforts to slice human time into thematic categories. Time and history are considered from the perspective of physics, archaeology, literature, western and Indigenous philosophy. Ultimately, this collection argues for imaginative new approaches to collaborative histories of deep time that are better suited to the challenges of the Anthropocene. Contributors to this volume, including many leading figures in their respective disciplines, consider history's temporality, and ask how history might expand to accommodate a chronology of deep time. Long histories that incorporate humanities, science and Indigenous knowledge may produce deeper meanings of the worlds in which we live.